Simplify :

A. (-2)(-3)

B. (-2)(3)

C. (2)(-3)

D.(2)(3)

A (-2)(-3) = 6

B. (-2)(3) = -6

C. (2)(-3) = -6

D.(2)(3) =6

Please let me know if you have any questions and best me if you are satisfactory.

would you be able to give me an explanation on how to complete these question aka shown work??

ya sure ..

Whenever you want to multiply two numbers with the same sign, the sign of the product is always positive.

so 2 * 3 = +6

= 6

Similarly -2 * -3 = +6 or simply 6

Whenever you want to multiply two numbers with different signs, the sign of the product is always negative.

so 2 * (-3) = -6

Similarly -2 * 3 = -6

BTW y have you posted the same question multiple times?

i have no idea on how and why that happened ;) a glitch perhaps

Thats ok....

Please let me know if you have any other questions.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up